La inclusión educativa en la Universidad Politécnica Salesiana:estudio de caso de un estudiante con enfermedad catastrófica - Terán Arias, Sara Nohemi (2017)
The educational inclusion in the Salesiana Polytechnic University (the inclusion case study of one student with catastrophic illness) The case analysis is a qualitative research tool, it studies situations that raise a problem, which must be understood, valued and solved by the person who makes the investigation. When the case analysis is done it will be investigated phenomena looking for answer the how and why they occur, being studied from different perspectives and a single variable; They allow deeply understand the singular fact (an individual, a group, a social situation or community), seeking solutions to the problem presented, for it must collect the information and be in contact with the object of study. Catastrophic Illness can become an obstacle for those who suffer from it, with a high possibility of abandoning their studies; this, in the Salesiana University, despite being inclusive has failed to achieve 100% inclusion for these students. Multiple factors trigger this problem to achieve full inclusion to the study process. This analyzes the importance of participating directly with the student through the planned accompaniment in which it is included is determined: interviews, observation of the student; log data obtained during the process of accompaniment; medical research disease "Pulmonary Dysplasia". Include the student in the educational system, being an independent, this process the student will be included in the educational community awareness